Enhancing Bachelor of Pharmacy program: Discussion with Pharmacy Stakeholders / Dr Mohd Shahezwan Abd Wahab ... [et al.] - Abd Wahab, Mohd Shahezwan; Osman, Nurul Izzati; Ahmad Kamal, Syahida Fathiah; Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2023)
On July 18th, 2023, the Faculty of Pharmacy at UiTM hosted a discussion session with Pharmacy Stakeholders, a ground-breaking initiative aimed at collecting valuable feedback and insights from representatives of various sectors within the pharmacy profession. The purpose of the session was also to evaluate how well the faculty's pharmacy program satisfies the expectations of stakeholders and to identify areas for improvement. Representatives from the community pharmacy, industrial pharmacy, and hospital pharmacy sectors, as well as the president of the Malaysian Pharmacists Society, Mr. Amrahi Buang attended the session. The session provided a forum for stakeholders to share their experiences, concerns, and suggestions regarding UiTM's current pharmacy program. Their firsthand knowledge provided valuable perspectives on the curriculum's strengths and shortcomings, the relevance of course content, and the required skills and competencies for future pharmacy professionals.